'But there are so many referrals which are totally … only generating work and irritation': a qualitative study of physicians' and nurses' experiences of work tasks in primary care in Sweden. (3rd July 2022) - Anskär, Eva; Falk, Magnus; Sverker, Annette
Abstract: Objective: This study explored the perceptions of physicians and nurses in Swedish primary care regarding the legitimacy of their work tasks and the use of their professional competence. Design and setting: This qualitative study was based on manifest content analysis. Data were collected with individual semi-structured interviews of physicians and nurses at publicly managed primary care centres in the Region Östergötland, Sweden. To include both large and small primary care centres, we applied strategic sampling. Among 15 primary care centres invited, nine agreed to participate, including four urban, two suburban, and three rural centres. Subjects: The study included 11 physicians and 13 nurses from nine primary care centres. Main outcome measures and results: The physicians and nurses perceived several of their work tasks as illegitimate. In addition, they experienced work-related difficulties, due to resource shortages, challenging electronic data systems, work inefficiencies, and that there were insufficient cooperation with, and problems drawing the line between, primary care and hospital care responsibilities. However, most found that their individual expertise was appropriately used, overall. Conclusions: Strained work situations and illegitimate work tasks may inflate discontentment and lead to negative work stress. Nevertheless, the staff felt that competence was used appropriately in the tasks considered legitimate. Key Points: Physicians and nurses in primary care in Sweden described several work tasks as illegitimate. Physicians and nurses described problems with heavy workloads, resource shortages, electronic data-system challenges, inefficiencies and with cooperation and drawing the line between primary care and hospital care. Overall, physicians and nurses believed their individual expertise was used appropriately. To uphold sustainable working conditions and thoughtful use of staff competence, organisational measures, such as redistributing staff from hospital to primary care were proposed.